The influence of product quality, celebrity endorser and brand image on decisions purchase scarlett whitening - Anastasya; Nur' Aeni (Jurnal Mantik, 2023)
Problem study This is is support quality celebrity endorser products , and image brand influence decision purchase , the purpose of this study was to determine the effect of product quality, celebrity endorser, and brand image on the purchase decision of Scarlett Whitening for Pelita University Management Study Program Students nation partially. The research method used in this research is quantitative research. The population used in this study were Pelita University Management Study Program students nation . The sampling method that the authors used in this research is the Accidental Sampling method, where the sample is Students of the Pelita University Management Study Program Nation which amounted to 100 respondents. The data collection method used in this research is primary data. The primary data taken is data from the answers of 100 respondents. The results of this study indicate that product quality has no positive and significant effect on the purchasing decision of Scarlett Whitening for Pelita University Management Study Program Students The nation is proven by the value of tcount <ttable or (1.508 <1.98 4). This is also reinforced by the Sig value. < 0.05 or (0.293 < 0.05). Supporters Celebrity There is no positive and significant effect on the purchasing decision of Scarlett Whitening for Students of the Lamp University Management Study Program as evidenced by tcount < ttable or (1.901 < 1.98 4). This is also reinforced by the Sig value. < 0.05 or (0.060 > 0.05). Brand Image has a positive and significant effect on the purchase decision of Scarlett Whitening for Students of the Lamp University Management Study Program as evidenced by tcount <ttable or (3.178 > 1.98 4). This is also reinforced by the Sig value. < 0.05 or (0.002 < 0.05).